A further catalysis mechanism study on Amberlyst 35 resins application in alkylation desulfurization of gasoline. (1st December 2015) - Wang, Rong; Wan, Jinbao; Li, Yonghong; Sun, Hongwei
Abstract: Olefinic alkylation of thiophenic sulfurs (OATS) technology can be handled under mild conditions without any hydrogen consumption, which is a promising way to produce clean gasoline. However, the side reaction in this desulfurization process would lead to significant levels of coke. To maintain the high activity for alkylation of sulfurs, the selectivity of OATS catalyst must be improved by reducing side reactions. In this paper, the catalytic mechanism of macroporous sulfonic resins Amberlyst 35 (A35) in the OATS process was further investigated by the calculation of density functional theory (DFT), to understand the reaction path of different reactant at molecular level. The calculated results indicated that the beginning of main and side reactions were both from a stable alkoxide intermediate, which was the protonation product of adsorbed olefin on the catalyst. Compared with alkenes, thiophenic compounds were more inclined to be coadsorbed on the alkoxide intermediate for further reaction, and the alkylation rate of sulfurs with alkenes was faster than the self-dimerization of alkenes. Moreover, the calculated results also indicated that the alkylation of thiophenic sulfurs as main reaction was exothermic while the dimerization of alkenes as side reaction was endothermic over A35. Additionally, the conversion curves of different reactants over A35 and the related kinetics at different temperature were also studied by experimental methods. The obtained experimental results could be used to verify the reliability of relevant theoretical calculations. Based on the differences in the reaction mechanisms obtained by the theoretical and experimental studies, two measures were proposed, which would be useful to reduce side reactions to a lower extent. The study would be beneficial to the further industrial application of A35 in the alkylation desulfurization of gasoline. Graphical abstract: Highlights: The catalysis mechanism of A35 in OATS process is studied by DFT method in depth. The path of main and side reactions over A35 is similar but there are two differences. Based on the differences, two methods are proposed to improve the selectivity of A35. The correctness of relevant theoretical calculations can be verified by experiments.